Free energy of binding of coiled-coil complexes with different electrostatic environments: the influence of force field polarisation and capping - Zhuo, Z.; Guo, L.; Mancera, Ricardo (Springer, 2014)
Coiled-coils are well known protein–protein interaction motifs, with the leucine zipper region of activator protein-1 (AP-1) consisting of the c-Jun and c-Fos proteins being a typical example. Molecular dynamics (MD) simulations using the MM/GBSA method have been used to predict the free energy of interaction of these proteins. The influence of force field polarisation and capping on the predicted free energy of binding of complexes with different electrostatic environments (net charge) were investigated. Although both force field polarisation and peptide capping are important for the prediction of the absolute free energy of binding, peptide capping has the largest influence on the predicted free energy of binding. Polarisable simulations appear better suited to determine structural properties of the complexes of these proteins while non-polarisable simulations seem to give better predictions of the associated free energies of binding